STATUS KETERAMPILAN TEKNIK DASAR BOLA BASKET PADA TIM ATLIT PUTRA PERSATUAN BOLA BASKET SELURUH INDONESIA (PERBASI) KABUPATEN SIAK - Murni Adinda; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Status basic engineering skills on the basketball team athlete son Persatuan Bola Basket Seluruh Indonesia (PERBASI) Kabupaten Siak. Skripsi. Jurusan Pendidikan Olahraga Universitas Riau. The problem in this research is unstability performance in playing basketball of team athlete son Persatuan Bola Basket Seluruh Indonesia (PERBASI) Kabupaten Siak. The Goal is to determine level or ranking basic engineering skills on the basketball team athlete son Persatuan Bola Basket Seluruh Indonesia (PERBASI) Kabupaten Siak. Sampling technique conducted with a total sampling totaling 12 athlete from team athlete son Persatuan Bola Basket Seluruh Indonesia (PERBASI) Kabupaten Siak. The data obtained in this research using the test and measurement of basic engineering skills of basketball with descriptive methods. Thus the overall category there was only one player (8,33%) categoried very well, 4 players (33,33%) well categoried, 5 players (41,67%) enough categoried, 2 players (16,67%) medium categoried, 0 player less categoried, 0 player less so categoried, and 0 player very less once categoried.Keyword: Status/position/ranking, skill basic technique playing basketball